Effectiveness Of Activity Programs Weekend Service in Fulfilling the Need for Population Administration Documents in Sidoarjo District - Aji, Bayu Purnomo; Tukiman, Tukiman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The research aims to determine how is the effectiveness public services at Sidoarjo’s Population and Civil Registrations service are in meeting needs population of administration document on weekend. Theoretical concept that used by researcher is from Joseph W. Duncan’s theory of effectiveness at Husna & Mayarni (2022) where the indicators of effectiveness is included: Achievement on the goals, Integration and Adapt of public service. Type of research used by researcher is descriptive qualitative method within sources and the type of data are divided into primary and secondary data through tooks activities documentation, employee interviews, and activity observe that’s can be used to draw a conclusion. Finding of the effectiveness research in the weekend activity are IKD activation and KTP recording on beginner are considered to haven’t been implemented properly in terms of factor that influence service regarding the lack of availability of facilities and infrastructures when activities take place and lack of communication, both to community and to stakeholder that maintain the system.